A model to resolve organochlorine pharmacokinetics in migrating humpback whales. (3rd June 2014) - Cropp, Roger; Nash, Susan Bengtson; Hawker, Darryl
Abstract Humpback whales are iconic mammals at the top of the Antarctic food chain. Their large reserves of lipid‐rich tissues such as blubber predispose them to accumulation of lipophilic contaminants throughout their lifetime. Changes in the volume and distribution of lipids in humpback whales, particularly during migration, could play an important role in the pharmacokinetics of lipophilic contaminants such as the organochlorine pesticide hexachlorobenzene (HCB). Previous models have examined constant feeding and nonmigratory scenarios. In the present study, the authors develop a novel heuristic model to investigate HCB dynamics in a humpback whale and its environment by coupling an ecosystem nutrient‐phytoplankton‐zooplankton‐detritus (NPZD) model, a dynamic energy budget (DEB) model, and a physiologically based pharmacokinetic (PBPK) model. The model takes into account the seasonal feeding pattern of whales, their energy requirements, and fluctuating contaminant burdens in the supporting plankton food chain. It is applied to a male whale from weaning to maturity, spanning 20 migration and feeding cycles. The model is initialized with environmental HCB burdens similar to those measured in the Southern Ocean and predicts blubber HCB concentrations consistent with empirical concentrations observed in a southern hemisphere population of male, migrating humpback whales. Results show for the first time some important details of the relationship between energy budgets and organochlorine pharmacokinetics. Environ Toxicol Chem 2014;33:1638–1649. © 2014 SETAC